Employee Health Screening in One of Iranian Gas Companies - shakiba bakhtom; ali amiri; sara tarokh (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Employee examination is one of the requirements of the occupational health care system. The present study aimed to evaluate the current health status of the staff working in an Iranian gas company to prevent, follow-up, and treat the disease. Methods: This cross-sectional descriptive-analytical study was conducted on the data collected from health screening of 94 service personnel in one of the gas companies in Iran. Data were collected by the 4-sheet forms of occupational examinations containing the following information: demographic data, general health status (blood pressure, smoking, allergy history, surgery, occupational accidents, body mass index), cardiovascular system, musculoskeletal, liver, kidney, gastrointestinal, clinical examination, paraclinical evaluations of the internal gland, cholesterol, triglycerides, liver enzymes, and hematopoietic system (CBC). Data were analyzed using SPSS 25. Results: All participants were male with an average (Standard Deviation) age and BMI of 42.96 ± 8.00 and26.83 ± 4.08, respectively. The participants' body mass index indicated that 45 staff (48.38%) were overweight and 15 individuals (16.12%) were in the range of obesity. The participants had history of smoking (22.3%), cholesterol above 200 (27.7%), and triglycerides above 300 (8/5%). The rate of hypermetropia, musculoskeletal disease, hypertension, high blood concentration and low blood platelets, hyperglycemia, cardiovascular disease, and kidney disease were 25.80%, 24.5%, 9.6%, 56.4%, 7.4%, 1.1%, and 12.8%, respectively. Conclusion: Although the studied company has a yearly occupational medical examination, the workers have not been provided with a comprehensive report and appropriate feedback. Therefore, it is essential to follow up the health reports and examinations and refer the patients to the related physicians.